Phylogenetic divergences of the true bugs (Insecta: Hemiptera: Heteroptera), with emphasis on the aquatic lineages: the last piece of the aquatic insect jigsaw originated in the Late Permian/Early Triassic. (18th September 2015) - Wang, Yan‐hui; Cui, Ying; Rédei, Dávid; Baňař, Petr; Xie, Qiang; Štys, Pavel; Damgaard, Jakob; Chen, Ping‐ping; Yi, Wen‐bo; Wang, Ying; Dang, Kai; Li, Chuan‐ren; et al.
Abstract: Heteroptera are among the most diverse hemimetabolous insects. Seven infraorders have been recognized within this suborder of Hemiptera. Apart from the well‐established sister‐group relationship between Cimicomorpha and Pentatomomorpha (= Terheteroptera), the two terminal lineages, the relationships among the other five infraorders are still controversial, of which three (Gerromorpha, Nepomorpha and Leptopodomorpha) are intimately connected to aquatic environments. However, the various and often conflicting available phylogeny hypotheses do not offer a clear background for a connection between diversification and palaeoenvironments. In this study, a molecular data set representing 79 taxa and 10 149 homologous sites is used to infer the phylogenetic relationships within Heteroptera. Bayesian inference, maximum‐likelihood and maximum parsimony analyses were employed. The results of phylogenetic inferences largely confirm the widely accepted phylogenetic context. Estimation of the divergence time based on the phylogenetic results revealed that Gerromorpha, Nepomorpha and Leptopodomorpha originated successively during the period from the Late Permian to Early Triassic (269–246 Ma). This timescale is consistent with the origin and radiation time of various aquatic holometabolans. Our results indicate that the aquatic and semi‐aquatic true bugs evolved under environmental conditions of high air temperature and humidity in an evolutionary scenario similar to that of the aquatic holometabolans.